The Influence Of Organizational Behavior Dimensions on Administrative and Financial Performance of Land Transportation Management Center - Hamka Husen; Marwan Marwan; Hendrian Hendrian (Green Publisher Indonesia, 2022)
This study aims to determine the effect of communication, motivation, and leadership on employee performance. This research was conducted at the Office of the Land Transportation Management Center Region XXIV, North Maluku Province, by taking research respondents as many as 73 people. This research method is a research hypothesis testing (hypothesis testing) which aims to test the hypothesis that was built using multiple regression analysis and the calculation operation using the SPSS program. The results of the research are as follows: (1). Communication has a significant positive effect on employee performance, with a total effect of 3.116. (2). Motivation has a significant positive effect on employee performance, with a total effect of 1,993. (3). Leadership has a significant positive effect on employee performance, with a total effect of 2,360. (4). Simultaneously there is a significant influence between communication, motivation, and leadership together on the performance of Administrative and Finance employees of the Land Transportation Management Center Region XXIV North Maluku Province with a determination contribution (R2) of 79.9%. The conclusion of this study is that it is proven that there is a significant influence between communication, motivation, and leadership on the performance of administrative and financial employees of the Land Transportation Management Center Region XXIV North Maluku Province.